Long-term exposure to PM2.5 and its constituents and visual impairment in schoolchildren: A population-based survey in Guangdong province, China - Jia-Hui Li; Hui-Xian Zeng; Jing Wei; Qi-Zhen Wu; Shuang-Jian Qin; Qing-Guo Zeng; Bin Zhao; Guang-Hui Dong; Ji-Chuan Shen; Xiao-Wen Zeng (Environment International)
Background: Exposure to fine particulate matter (PM2.5) has been linked to visual impairment. Nevertheless, evidence associating PM2.5 constituents with visual impairment in schoolchildren is sparse. Objectives: To explore the effects of long-term exposure to PM2.5 and its constituents on visual impairment. Methods: We conducted a large cross-sectional population-based study to recruit 59,054 schoolchildren from four cities in Guangdong province, China, and used the ChinaHighAirPollutants (CHAP) dataset to estimate 3-year average concentrations of PM2.5 and its constituents (black carbon (BC), organic matter (OM), nitrate (NO3–), sulfate (SO42−) and ammonium (NH4+)) based on individuals’ home addresses. Visual acuity was measured with a standardized logarithmic chart, and visual impairment was defined as visual acuity below 4.9 (Snellen 5/6 equivalent) in at least one eye. We utilized generalized linear mixed models and weighted quantile sum regression to assess the association between PM2.5 constituents and visual impairment. Results: The observed associations typically displayed a nonlinear pattern. Compared to the lowest quartile of PM2.5 and its constituents, the fourth quartile was associated with higher odds of visual impairment in schoolchildren (e.g., the adjusted odds ratio (OR) was 1.23 (95% CI: 1.13, 1.33) for PM2.5, 1.53 (95% CI: 1.40, 1.67) for OM, and 1.35 (95% CI: 1.27, 1.44) for BC), respectively. Similarly, joint exposure to PM2.5 constituents was associated with visual impairment (OR = 1.17, 95% CI: 1.13, 1.22), while BC and OM contributed more to the observed associations. Conclusions: Long-term exposure to PM2.5 and its constituents was significantly associated with higher rates of visual impairment in schoolchildren, with combustion-related BC and OM potentially driving the observed associations.